The Control of Dengue Hemorrhagic Fever Using Innovations For The Integrated Controlling Aedes Mosquitoes - Tawatsin, Apiwat; Thavara, Usavadee; Yowang, Amara; Jitphayak, Udon; Srivarom, Navy (British Journal of Healthcare and Medical Research, 2024)
Dengue hemorrhagic fever (DHF) is an infectious disease transmitted to humans by Aedes aegypti and Ae. albopictus mosquitoes. The prevention and control of these vector mosquitoes are the main strategies to control the disease since no effective vaccine is available for prevention. This project aimed to reduce the Aedes mosquito populations in the study areas using the three innovations of the Department of Medical Sciences (LeO-Trap: lethal ovitrap, AZAI: Aedes larvicide, and RepelMos: mosquito repellent) with community participation. The study was conducted in Chiang Rai Province (Muang District) and Phrae Province (Muang District and Song District) as these provinces were predicted as the potentially epidemic areas of DHF in 2022. The study areas were 2 villages (approximately 100 houses/village) selected from each District; as a result, 815 houses from these 6 villages participated in this study. The owner of each house received 4 sets of LeO-Trap (2 traps for use inside the house and 2 traps for use outside the house), 4 bags (100 g.) of AZAI, and 2 bottles (40 ml.) of RepelMos. Overall, the village health volunteers collected the sponge sheets (substrate for egg laying of Aedes mosquitoes) from the total treated houses ranged from 78% to 100% while the houses positive for Aedes eggs were between 29.6% and 100%. The total number of Aedes eggs collected from inside and outside the houses of the 6 villages in this study was 282,160 eggs; therefore, it could be estimated that 70,540,000 Aedes mosquitoes were rid of by the LeO-Trap in the study areas based on the assumption that a female mosquito could produce 500 offspring in her lifetime. Regarding the data collected by Sub-district, the highest numbers of Aedes eggs were collected from Nang Lae Sub-district in Muang District, Chiang Rai Province (117,557 eggs with an average 87 eggs/house), followed by Hua Muang Sub-district in Song District, Phrae Province (99,326 eggs with an average 97 eggs/house) and Mae Kam Mee Sub-district in Muang District, Phrae Province (65,277 eggs with an average 62 eggs/house). Overall, the number of Aedes eggs collected by the LeO-Trap inside the houses was higher than those obtained outside the houses in the three sub-districts. The results obtained from this study indicated that the innovations used in this project with community participation could substantially reduce Aedes mosquito populations in the study areas and reduce the incidence of DHF. This study could be a model for preventing and controlling Aedes mosquitoes in other areas.